De-novo computational design of peptides for the specific and selective recognition of small molecules - Pereira, José Manuel Santos (2023)
The main objective of this PhD thesis was the computational design of peptides for the specific and selective recognition of small molecules. In the last decades, the field of computational protein design has seen massive developments both at the hardware and software level. Some of the most commonly used tools, however, have lagged behind in comparison with the expectations of a modern protein design software: speed, simplicity and a wide range of features. In that regard, and on the scope of the present thesis, a new solution for the computational design of proteins was envisioned, named ProtoSyn.jl. This tool, developed in a model programming language (Julia), intends to facilitate the manipulation and simulation of molecular systems, with a clear emphasis on the rational design of proteins. The proposed work was divided into 4 stages: (i) The definition of a base architecture for ProtoSyn.jl, including data structures representative of molecular systems and all the code related to the simulation of said systems; (ii) the development of numerical optimization algorithms based on SIMD, GPU and distributed computing technologies for the calculation of non-bonded atomic interactions in molecular systems; (iii) The development and parametrization of energy function components for the iterative evaluation of molecular structures; (iv) The application of the developed program in practical simulation use-cases, namely a) sidechain repackaging, b) protein folding prediction, c) amino acid sequence recovery, d) small molecule docking and, finally, e) rational design of peptides for the recognition of small molecules. In short, this PhD thesis was based on a multidisciplinary approach, distributed between the fields of computational chemistry and computer sciences. Its main result is ProtoSyn.jl: a novel API for molecular manipulation and simulation, constituting a modern solution that allows and facilitates the composition of arbitrarily complex simulation protocols in a simple and modular fashion. Furthermore, several practical applications of the program are presented, culminating on the definition of a protein design candidate library for the specific recognition of a small molecule on the surface of a peptide.